PENGARUH SUHU TERHADAP PERKEMBANGAN EMBRIO DAN STADIA AWAL LARVA IKAN TUNA SIRIP KUNING (Thunnus albacares) - Tiara Kusuma Wardani (Universitas Mataram, 2019)
The purpose of this study, to determine the effect of temperatura on embryonic development and early stadia larvae of yellow fin tuna (Thunnus albacares) and the level abnormalities of the larvae. This research was carried out in a Large Marine Aquaculture Center And Hyacinth Fisheries Gondol. The container used is a 1 liter backer glass of 15 pieces. Egg density at each backer glass is 300 grains. The temperature treatment used is (240C±1), P2 (260C±1), P3 (280C±1), P4 (300C±1), P5 (320C±1). Parameters observed were egg hatchability, egg hatching time, larval abnormalities, absorption of egg yolk and larval length. Based on the result of the study showed that different temperature treatments were able to give a significant influence on the development of eggs and the time of hatching egg. The temperature treatment 260C was able to increase the hatchbility value by 40,7%, larvae abnormality value 15,8%, larvae length growth 5,48 mm compared to other temperature treatment. The best egg yolk absorption rate is shown at the temperature treatment of 240C, 260C, and 280C compared to the 300C and 320C temperature treatments.